Are U.S. Companies Really Holding That Much Cash—And If So, Why?. Issue 1 (March 2016) - Zenner, Marc; Junek, Evan; Chivukula, Ram
Abstract : Non‐financial S&P 500 companies are now estimated to hold a total of $2.1 trillion of "cash, " a figure that is larger than the annual GDP of all but eight countries. In this report, J.P. Morgan's Corporate Finance Advisory team notes that while many observers have attributed the buildup to offshore cash growth alone, onshore cash levels are also up significantly. To be sure, the companies that have shown the greatest increases also tend to be highly successful, with strong cash flow and business performance. And the managers of such companies tend to prefer to retain much if not most of this cash to take advantage of investment opportunities and to maintain the flexibility to respond to the next economic downturn. Also adding to the cash build‐ups, the executives of large MNCs with significant overseas cash holdings typically try to avoid the higher tax bill triggered by repatriating funds to the U.S. Nevertheless, investors continue to expect growth and high returns on capital; and corporate distributions of capital in the form of dividends and stock buybacks can play an important role in encouraging companies to operate efficiently. While pursuing both of these goals—preservation of enough cash to weather downturns and invest in all positive‐NPV projects, and commitment to paying out excess capital—boards and senior decision makers should continuously reexamine their cash holdings and capital allocation policies to ensure they are appropriate not only for today's environment, but throughout the economic cycle.